The Innovative Leadership Model Of Pesantren In Developing The Potential Of Gifted Students - Riswanda Maulana, Muhammad; Manumanoso Prasetyo, Muhammad Anggung; Rizki Jailani, Munawar (The Faculty of Education and Teaching Training, 2024)
The attractiveness of pesantren is determined through the quality of graduates. The talent interest factor requires innovative policy support. This study aims to explore the implementation of innovative leadership and describe the characteristics of innovative leadership in developing the potential of talented santri at Almuslim Peusangan Bireun Islamic boarding school. The sources of informants in this study are the head of the care sector, the head of the teaching sector, the supervisor of the santri organization, and the supervisor of the santri talent interest section. The research method used is qualitative with a case study approach located at the Almuslim Peusangan Bireun Integrated Islamic Boarding School. The results of this study found that the leader of the Al Muslim integrated pesantren applies innovative leadership characteristics, 1) The innovations made are, a). Creating a digitalization program in learning, b). Creating a santri entrepreneur program, c). And increasing the potential of students. 2) Increasing the competence of santri is done through, a). External and internal support (cooperation), b). Development of individual potential, c). Development of institutional potential.